High-Sensitivity, Low Detection Limit, and Fast Ammonia Detection of Ag-NiFe2O4 Nanocomposite and DFT Study - Xianfeng Hao; Yuehang Sun; Zongwei Liu; Gongao Jiao; Dongzhi Zhang (Nanomaterials)
Ammonia (NH3) is one of the characteristic gases used to detect food spoilage. In this study, the 10 wt% Ag-NiFe2O4 nanocomposite was synthesized via the hydrothermal method. Characterization results from SEM, XRD, and XPS analyzed the microstructure, elemental composition, and crystal lattice features of the composite, confirming its successful fabrication. Under the optimal working temperature of 280 °C, the composite exhibited excellent gas-sensing properties towards NH3. The 10 wt% Ag-NiFe2O4 sensor demonstrates rapid response and recovery, as well as high sensitivity, towards 30 ppm NH3, with response and recovery times of merely 3 s and 9 s, respectively, and a response value of 4.59. The detection limit is as low as 0.1 ppm, meeting the standards for food safety detection. Additionally, the sensor exhibits good short-term repeatability and long-term stability. Additionally, density functional theory (DFT) simulations were conducted to investigate the gas-sensing advantages of the Ag-NiFe2O4 composite by analyzing the electron density and density of states, thereby providing theoretical guidance for experimental testing. This study facilitates the rapid detection of food spoilage and promotes the development of portable food safety detection devices.